Strong Key Organization & Protected Statistics Shift System for VANET - K. Rameshwaraiah (International Journal of Intelligent Systems and Applications in Engineering, 2024)
VANETs are integral to vehicle control systems, allowing vehicles to communicate with one another in a centralized manner. This communication enhances coordination and safety, but also introduces potential cyber security risks. To protect the vehicle infrastructure, it is crucial to develop effective security solutions, as cyber-attacks on VANETs can lead to significant financial losses and safety hazards. Field devices within VANETs, which rely on microcontrollers for processing information, face challenges due to their limited computational capabilities and resources, making it difficult to implement sophisticated security measures. This academic work introduces a novel multi-tiered framework that merges symmetric and asymmetric input cryptographic methods. Our method promise accessibility, reliability, privacy, confirmation. The recommended modified assembly input organization device to merge accidental numeral making by jumble communication confirmation system. Furthermore, we incorporate three distinct symmetric key cryptographic methods inspired by the Vernam cipher, enhancing security with a arbitrary major figure originator, major contradict, plus hash chaining.